Active material and preparation method thereof, secondary battery and capacitor
The method of heat-treating a mixture of porous carbon and metal salts with alkali metals addresses the energy and power density limitations of second batteries and capacitors, resulting in enhanced storage capacity and stability.
Patent Information
- Application Number
- CN202411488386.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-03-14
AI Technical Summary
Current second batteries and capacitors face limitations in energy density and power density, with lithium-ion batteries having low power density and capacitors having low energy density, hindering their performance in fast charging and energy storage applications.
A method for preparing active materials by mixing porous carbon with metal salts and alkali metals, followed by heat treatment under controlled pressure and temperature, leading to the formation of a new carbon material layer that enhances mechanical strength, conductivity, and storage capacity.
The method results in active materials with improved electronic conductivity, mechanical strength, and storage capacity, enhancing the performance of both second batteries and capacitors in terms of energy density and cycle stability.
Smart Images

Figure CN119627063A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of energy storage, and in particular, to active materials and preparation methods thereof, secondary batteries and capacitors. Background Art
[0002] Secondary batteries and capacitors each have their own advantages and limitations in the field of energy storage. Secondary batteries, such as lithium-ion batteries, are favored for their high energy density and are widely used in fields such as mobile devices and electric vehicles. However, the power density of lithium-ion batteries is relatively low, which limits their development in the field of fast charging. In contrast, capacitors have high power density and the ability to charge and discharge quickly, but the energy density of capacitors is low. Therefore, there is an urgent need to improve secondary batteries or capacitors to meet the growing energy demand.
[0003] It should be noted that the above statements are only used to provide background technical information related to the present application and do not necessarily constitute prior art. Summary of the invention
[0004] In the first aspect of the present application, the present application provides a method for preparing an active material, comprising: mixing porous carbon and a nucleating agent to obtain a mixture; wherein the nucleating agent includes at least one of an alkaline earth metal, an alkali metal, and a transition metal salt; calcining the mixture to obtain the active material; wherein the calcination pressure is 0.02MPa-1MPa; and the calcination temperature is 300℃-2000℃.
[0005] Thus, the nucleating agent is first fully mixed with the porous carbon, so that the nucleating agent is attached to the surface of the porous carbon or anchored in the pores of the porous carbon; under the action of high temperature, part of the carbon components of the porous carbon will be pyrolyzed to form the carbon source itself, and at the same time, the newly generated carbon source takes the nucleating agent as the nucleation growth center and is deposited on the new surface or pores of the porous carbon to form a new carbon material layer, and under the action of pressure, the newly generated carbon material is promoted to grow densely, and the newly generated carbon material layer can not only slow down the further decomposition of the porous carbon, but also block the open pores of the porous carbon, thereby improving the pore structure of the porous carbon. The formed carbon material layer not only has high crystallinity and hardness, but also has good conductivity and mechanical properties, so it can enhance the mechanical strength of the porous carbon, reduce the surface defects of the porous carbon, and thus improve the lithium storage performance of the active material.
[0006] In some embodiments, the calcination temperature is 500° C.-1300° C., and the calcination time is 0.5 h-10 h. Thus, the mechanical strength of the porous carbon can be further enhanced, and the surface defects of the porous carbon can be reduced, thereby improving the lithium storage performance of the active material.
[0007] In some embodiments, the mass ratio of the porous carbon to the nucleating agent in the mixture is 1:(0.01-0.1). Thus, by controlling the ratio of the porous carbon to the nucleating agent, the nucleation and growth of the carbon material layer on the surface of the porous carbon can be promoted, thereby improving the nucleation efficiency.
[0008] In some embodiments, the transition metal salt includes at least one of chlorate, sulfate, nitrate, and phosphate of a transition metal element; the transition metal element includes at least one of manganese, cobalt, nickel, iron, zinc, and copper. Thus, selecting a transition metal salt of suitable material can further promote the re-growth of a carbon material layer on the surface of the porous carbon, thereby adjusting the pore structure of the porous carbon, enhancing the mechanical strength of the porous carbon, and reducing the surface defects of the porous carbon.
[0009] In some embodiments, the alkali metal includes at least one of lithium metal, sodium metal, and potassium metal. Thus, selecting an alkali metal of suitable material can further promote the re-growth of a carbon material layer on the porous carbon surface. At the same time, the molten alkali metal can promote the reorganization of the newly grown carbon material structure and improve the graphitization degree of the porous carbon.
[0010] In some embodiments, the alkaline earth metal includes at least one of metal magnesium and metal calcium. Thus, selecting an alkaline earth metal of suitable material can further promote the re-growth of a carbon material layer on the surface of the porous carbon. At the same time, the molten alkali metal can promote the reorganization of the carbon atom structure of the porous carbon part and improve the graphitization degree of the porous carbon.
[0011] In some embodiments, the Dv50 particle size of the nucleating agent is 1 nm-10 nm. Thus, selecting a nucleating agent with a suitable particle size can provide more active sites for subsequent catalytic reactions, thereby improving catalytic efficiency.
[0012] In some embodiments, the porous carbon includes at least one of biomass-based porous carbon, resin-based porous carbon, and petroleum asphalt-based porous carbon. Porous carbon materials are widely available and have low costs, and different types of porous carbon have different pore structure characteristics, such as pore size, pore distribution, etc. Therefore, selecting a suitable porous carbon material can adjust the pore structure, specific surface area, and electrochemical performance of the active material to meet different working requirements.
[0013] In some embodiments, the specific surface area of the porous carbon is 500 m 2 / g-1000m 2 Therefore, by selecting porous carbon with a suitable specific surface area, more attachment sites can be provided for the nucleating agent while maintaining the stability of the porous carbon structure.
[0014] In some embodiments, before the calcination process, the method further comprises: drying the mixed material, wherein the drying temperature of the drying process is 80° C. to 120° C. Thus, the water content in the mixed material can be reduced.
[0015] In some embodiments, the method further comprises post-processing the active material, wherein the post-processing step comprises: washing the active material with an acidic solution, thereby separating the nucleating agent from the active material.
[0016] In a second aspect of the present application, the present application provides an active material prepared by the above method, wherein the prepared active material has high electronic conductivity and good lithium storage capacity.
[0017] In the third aspect of the present application, the present application provides a secondary battery, comprising a negative electrode plate, the negative electrode plate comprising a negative electrode current collector, and a negative electrode active material layer located on at least one side of the negative electrode current collector, the negative electrode active material layer comprising an active material prepared by the aforementioned method, or the aforementioned active material. As a result, the secondary battery of the present application has the advantages of good lithium storage capacity, good charge retention capacity and good cycle stability, meeting the needs of high-energy, long-life batteries.
[0018] In a fourth aspect of the present application, the present application provides a capacitor, comprising an electrode plate, wherein the electrode plate comprises an active material layer, wherein the active material layer comprises an active material prepared by the aforementioned method, or the aforementioned active material. Thus, the capacitor of the present application has the advantages of higher energy density and good cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0020] Figure 1 It is a schematic diagram of the process flow for preparing active materials in one embodiment of the present application. DETAILED DESCRIPTION
[0021] Below, the active material and its preparation method, secondary battery and capacitor of the present application are described in detail with appropriate reference to the drawings. However, there are cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0022] " Scope " disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be to include end values or not include end values, and can be combined arbitrarily, that is, any lower limit can form a scope with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for a particular parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 listed, and if the maximum range values 3,4 and 5 are listed, the following scope can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0023] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0024] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0025] Unless otherwise defined, all technical and scientific terms used in this application have the same meanings as those commonly understood by technicians in the technical field to which this application belongs; the terms used in this application are only for the purpose of describing specific embodiments and are not intended to limit this application; unless otherwise specified, the numerical values of the parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the embodiments of this application).
[0026] In the description of this application, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. "First feature" and "second feature" may include one or more of the features.
[0027] In the description of the present application, "A and / or B" may include the case of A alone, the case of B alone, or any of the cases of A and B, where A and B are only used for examples and may be any technical feature connected by "and / or" in the present application.
[0028] Porous carbon materials have attracted much attention in the field of energy storage, especially in the field of secondary batteries and capacitors, due to their tunable physical and chemical properties, fast electron or ion transmission channels, and excellent cost-effectiveness. However, porous carbon materials also have limitations. For example, porous carbon materials have a large specific surface area, and there are many structural defects on the porous carbon surface, which leads to low reversible capacity and poor cycle stability of lithium-ion batteries when porous carbon materials are used as negative electrode materials for lithium-ion batteries; porous carbon materials have a low degree of graphitization, poor electrical conductivity, and uneven pore structure distribution, which leads to the porous carbon materials being used as active materials for capacitors. The ion transmission rate of the capacitor is affected, which in turn affects the charge and discharge efficiency and cycle stability of the capacitor. Therefore, in order to meet the growing energy demand, it is very necessary to modify porous carbon materials to improve the performance of secondary batteries and capacitors.
[0029] In a first aspect of the present application, the present application provides a method for preparing an active material, referring to Figure 1 , the method comprising:
[0030] S100, the porous carbon and the nucleating agent are mixed to obtain a mixture.
[0031] In some embodiments, the porous carbon includes at least one of biomass-based porous carbon, resin-based porous carbon, and petroleum asphalt-based porous carbon. Porous carbon materials are widely available and have low costs, and different types of porous carbon have different pore structure characteristics, such as pore size, pore distribution, etc. Therefore, selecting a suitable porous carbon material can adjust the pore structure, specific surface area, and electrochemical performance of the active material to meet different working requirements.
[0032] In some embodiments, the specific surface area of the porous carbon is 500 m 2 / g-1000m 2 Therefore, by selecting porous carbon with a suitable specific surface area, more attachment sites can be provided for the nucleating agent while maintaining the stability of the porous carbon structure.
[0033] As an example, the specific surface area of porous carbon can be 500 m 2 / g、600m 2 / g、700m 2 / g、800m 2 / g、900m 2 / g or 1000m 2 / g.
[0034] In some embodiments, the nucleating agent comprises a transition metal salt. Thus, the nucleating agent is mixed with the porous carbon using a liquid phase blending technique.
[0035] In some embodiments, the liquid phase blending technology includes: first preparing the nucleating agent into a nucleating agent solution, then adding the porous carbon into the nucleating agent solution and stirring to obtain a mixed solution; and drying the mixed solution to obtain a mixture. In this way, the nucleating agent and the porous carbon can be fully mixed, so that the nucleating agent is attached to the surface of the porous carbon or anchored in the pores of the porous carbon.
[0036] As an example, the stirring speed of the stirring process is 50r / min-200r / min, the stirring time is 4h-10h, and the stirring temperature is 20℃-30℃. The stirring speed includes but is not limited to 50r / min, 100r / min, 150r / min or 200r / min; the stirring time includes but is not limited to 4h, 5h, 6h, 7h, 8h, 9h or 10h; the stirring temperature includes but is not limited to 20℃, 22℃, 24℃, 26℃, 28℃ or 30℃.
[0037] As an example, the drying temperature of the drying process is 80° C.-120° C. The drying temperature includes, but is not limited to, 80° C., 90° C., 100° C., 110° C. or 120° C.
[0038] As an example, the solvent used to formulate the nucleating agent solution includes water.
[0039] In some embodiments, the transition metal salt includes at least one of chlorate, sulfate, nitrate, and phosphate of the transition metal element; the transition metal element includes at least one of manganese, cobalt, nickel, iron, zinc, and copper. Thus, selecting a transition metal salt of suitable material can further promote the re-growth of a carbon material layer on the surface of the porous carbon, thereby adjusting the pore structure of the porous carbon, enhancing the mechanical strength of the porous carbon, and reducing the surface defects of the porous carbon.
[0040] In some embodiments, the nucleating agent comprises an alkaline earth metal and / or an alkali metal. Thus, the nucleating agent is mixed with the porous carbon using a solid phase blending technique.
[0041] In some embodiments, the solid phase blending technique comprises: grinding the nucleating agent and the porous carbon in a glove box for 20 min to 90 min to obtain a mixture.
[0042] As an example, the grinding time includes, but is not limited to, 20 min, 30 min, 40 min, 60 min, 70 min, 80 min or 90 min.
[0043] In some embodiments, the alkali metal includes at least one of lithium metal, sodium metal, and potassium metal. Thus, selecting an alkali metal of suitable material can further promote the re-growth of a carbon material layer on the porous carbon surface. At the same time, the molten alkali metal can promote the reorganization of the newly grown carbon material structure and improve the graphitization degree of the porous carbon.
[0044] In some embodiments, the alkaline earth metal includes at least one of metal magnesium and metal calcium. Thus, selecting an alkaline earth metal of suitable material can further promote the re-growth of a carbon material layer on the surface of the porous carbon, and at the same time, the molten alkali metal can promote the reorganization of the carbon atom structure of the porous carbon part, thereby improving the graphitization degree of the porous carbon.
[0045] In some embodiments, the nucleating agent has a Dv50 particle size of 1 nm to 10 nm.
[0046] As an example, the Dv50 particle size of the nucleating agent can be 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm or 10 nm. Thus, selecting a nucleating agent with a suitable particle size can provide more active sites for subsequent catalytic reactions, thereby improving catalytic efficiency.
[0047] In some embodiments, the mass ratio of porous carbon to nucleating agent in the mixture is (2-10): 1. Thus, by controlling the ratio of porous carbon to nucleating agent, the nucleation and growth of the carbon material layer on the surface of porous carbon can be promoted, thereby improving the nucleation efficiency.
[0048] S200, calcining the mixed material to obtain an active material.
[0049] In some embodiments, the temperature of the mixture is raised to the calcination temperature by heating, and the heating rate of the heating treatment is 0.5°C / min-10°C / min. Thus, the slow heating rate helps to reduce the thermal stress of the mixture caused by the rapid temperature change, thereby reducing the risk of porous carbon cracking.
[0050] In some embodiments, the heating rate of the temperature rising treatment can be 0.5°C / min, 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min or 10°C / min.
[0051] In some embodiments, the temperature treatment is performed in a protective atmosphere, so that the protective atmosphere prevents the mixed material from undergoing an oxidation reaction with oxygen in the air under a high temperature environment.
[0052] In some embodiments, the protective atmosphere includes at least one of a hydrogen-argon mixed gas, a hydrogen-nitrogen mixed gas, nitrogen, and argon.
[0053] In some embodiments, when the protective atmosphere contains hydrogen, the concentration of hydrogen in the protective atmosphere is 1%-10%.
[0054] As an example, the concentration of hydrogen in the protective atmosphere may be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%.
[0055] In some embodiments, the calcination temperature is 300° C.-2000° C., and the calcination time is 0.5 h-10 h.
[0056] Due to the unstable chemical bonds in porous carbon or the residual incompletely carbonized precursor components, part of the carbon components of porous carbon will be pyrolyzed under high temperature to form the carbon source itself. When the nucleating agent includes a transition metal salt, the newly generated carbon source takes the nucleating agent as the nucleation growth center and is deposited on the new surface and pores of the porous carbon to form a new carbon material layer. The newly generated carbon material layer can not only slow down the further pyrolysis of porous carbon, but also block the open pores of porous carbon, thereby improving the pore structure of porous carbon; when the nucleating agent includes alkaline earth metal and / or alkali metal, the nucleating agent is first melted under high temperature to fully mix the nucleating agent and porous carbon, and the molten nucleating agent adheres to the surface of porous carbon or anchors in the pores of porous carbon; then, part of the carbon components of porous carbon are slowly pyrolyzed into new carbon sources under high temperature, and at the same time, the newly generated carbon source takes the nucleating agent as the nucleation growth center and is deposited on the new surface and pores of porous carbon to form a new carbon material layer; and the molten nucleating agent promotes the reorganization of the structure of the newly generated carbon material, so that the porous carbon is transformed from an amorphous carbon structure to an ordered arrangement structure, thereby improving the degree of graphitization of the porous carbon and reducing the surface defects of the porous carbon.
[0057] As an example, the temperature of the calcination treatment may be 300°C, 400°C, 500°C, 600°C, 700°C, 800°C, 900°C, 1000°C, 1100°C, 1200°C, 1300°C, 1400°C, 1500°C, 1600°C, 1700°C, 1800°C, 1900°C or 2000°C.
[0058] As an example, the calcination treatment time may be 0.5 h, 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h or 10 h.
[0059] In some embodiments, the calcination process is performed at a pressure of 0.02 MPa to 1 MPa.
[0060] When the nucleating agent includes a transition metal salt, the pressure promotes the dense growth of the newly generated carbon material, thereby further improving the crystallinity and hardness of the carbon material layer, further improving the pore structure of the porous carbon, and reducing the surface defects of the porous carbon.
[0061] When the nucleating agent includes alkaline earth metal and / or alkali metal, the pressure squeezes the molten nucleating agent and the newly generated carbon material, further reducing the surface defects of the porous carbon, and the porous carbon can maintain a larger specific surface area.
[0062] As an example, the pressure of the calcination process may be 0.02 MPa, 0.04 MPa, 0.06 MPa, 0.08 MPa, 0.1 MPa, 0.2 MPa, 0.3 MPa, 0.4 MPa, 0.5 MPa, 0.6 MPa, 0.7 MPa, 0.8 MPa, 0.9 MPa or 1 MPa.
[0063] In some embodiments, the aforementioned method further comprises post-processing the active material, thereby separating the nucleating agent from the active material.
[0064] In some embodiments, the post-treatment step includes: washing the active material with an acidic solution, filtering, and drying the filtrate, thereby removing the nucleating agent on the porous carbon surface.
[0065] As an example, the acidic solution includes at least one of a sulfuric acid solution, a hydrochloric acid solution, and a nitric acid solution.
[0066] As an example, the concentration of the acidic solution is 0.2 mol / L-1 mol / L. The concentration of the acidic solution includes, but is not limited to, 0.2 mol / L, 0.4 mol / L, 0.6 mol / L, 0.8 mol / L or 1 mol / L.
[0067] In a second aspect of the present application, the present application provides an active material prepared by the above method, wherein the prepared active material has high electronic conductivity and good lithium storage capacity.
[0068] In the third aspect of the present application, the present application provides a secondary battery, including a negative electrode plate, the negative electrode plate including a negative electrode current collector, and a negative electrode active material layer located on at least one side of the negative electrode current collector, the negative electrode active material layer including an active material prepared by the aforementioned method, or the aforementioned active material. As a result, the secondary battery of the present application has the advantages of good lithium storage capacity, good charge retention capacity and good cycle stability, meeting the needs of high-energy, long-life batteries.
[0069] In some embodiments, the current collector comprises copper foil.
[0070] In some embodiments, the negative electrode active material layer may further include a binder, for example, the binder includes at least one of sodium carboxymethyl cellulose, polyacrylic acid, sodium alginate, and polyvinylidene fluoride.
[0071] In some embodiments, the negative electrode active material layer may further include a conductive agent. As an example, the conductive agent includes at least one of acetylene black, Ketjen black, and Super P carbon black.
[0072] In some embodiments, in the negative electrode active material layer, the mass ratio of the negative electrode active material to the binder is (6-9):(0.5-2). As an example, the mass ratio of the negative electrode active material to the binder includes but is not limited to 6:0.5, 6:1, 6:2, 7:0.5, 7:1, 7:2, 8:0.5, 8:1, 8:2, 9:0.5, 9:1, 9:2.
[0073] In some embodiments, in the negative electrode active material layer, the mass ratio of the negative electrode active material to the conductive agent is (6-9):(0.5-2). As an example, the mass ratio of the negative electrode active material to the conductive agent includes but is not limited to 6:0.5, 6:1, 6:2, 7:0.5, 7:1, 7:2, 8:0.5, 8:1, 8:2, 9:0.5, 9:1, 9:2.
[0074] In some embodiments, the secondary battery further includes a separator and an electrolyte.
[0075] In some embodiments, the separator includes at least one of PP, PE, and a ceramic membrane. Preferably, the separator is PP.
[0076] In some embodiments, the electrolyte includes a lithium salt, an additive, and a non-aqueous solvent.
[0077] In some embodiments, the lithium salt includes at least one of LiPF6, LiFSI, and LiTFSI. Preferably, the lithium salt is LiPF6.
[0078] In some embodiments, the additive includes at least one of fluoroethylene carbonate, trimethyl phosphate, ethylene carbonate, and ethyl hexafluorophosphate. Preferably, the additive is a mixture of 10% fluoroethylene carbonate (FEC) and 1% ethylene carbonate (VC).
[0079] In some embodiments, the non-aqueous solvent includes at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, and diethyl carbonate. Preferably, the non-aqueous solvent is a mixed solution of diethyl carbonate and ethylene carbonate in a volume ratio of 1:1.
[0080] In some embodiments, the concentration of the lithium salt in the electrolyte is 0.5 mol / L-2 mol / L. As an example, the concentration of the lithium salt may be 0.5 mol / L, 1 mol / L, 1.5 mol / L or 2 mol / L. Preferably, the concentration of the lithium salt is 1 mol / L.
[0081] In some embodiments, the negative electrode sheet can be prepared by the following method: the active material, binder, and conductive agent prepared by the above method are formulated into a slurry, and the slurry is applied to the surface of at least one side of the current collector; after the slurry is dried, the negative electrode sheet is obtained.
[0082] In some embodiments, the solvent of the slurry includes water and / or N-methylpyrrolidone (NMP).
[0083] In some embodiments, the drying temperature of the slurry is 60°C-120°C.
[0084] As an example, the drying temperature of the slurry may be 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, or 120°C.
[0085] In some embodiments, the drying time of the slurry is 1 h to 20 h.
[0086] As an example, the drying time of the slurry may be 1 h, 2 h, 4 h, 6 h, 8 h, 10 h, 12 h, 14 h, 16 h, 18 h or 20 h.
[0087] In a fourth aspect of the present application, the present application provides a capacitor, comprising an electrode plate, the electrode plate comprising an active material layer, the active material layer comprising an active material prepared by the aforementioned method, or the aforementioned active material. Thus, the capacitor of the present application has the advantages of higher energy density and good cycle stability.
[0088] In some embodiments, the capacitor includes a supercapacitor, and the electrode plate of the present application can be used as both the negative electrode plate and the positive electrode plate of the supercapacitor.
[0089] In some embodiments, the active material layer may further include a binder, for example, the binder includes at least one of sodium carboxymethyl cellulose, polyacrylic acid, sodium alginate, and polyvinylidene fluoride.
[0090] In some embodiments, the active material layer may further include a conductive agent. As an example, the conductive agent includes at least one of acetylene black, Ketjen black, and Super P carbon black.
[0091] In some embodiments, in the active material layer, the mass ratio of the active material to the binder is (6-9):(0.5-2). As an example, the mass ratio of the active material to the binder includes but is not limited to 6:0.5, 6:1, 6:2, 7:0.5, 7:1, 7:2, 8:0.5, 8:1, 8:2, 9:0.5, 9:1, 9:2.
[0092] In some embodiments, in the active material layer, the mass ratio of the active material to the conductive agent is (6-9):(0.5-2). As an example, the mass ratio of the active material to the conductive agent includes but is not limited to 6:0.5, 6:1, 6:2, 7:0.5, 7:1, 7:2, 8:0.5, 8:1, 8:2, 9:0.5, 9:1, 9:2.
[0093] In some embodiments, the capacitor further includes a current collector, a separator, and an electrolyte.
[0094] In some embodiments, the current collector includes at least one of a stainless steel mesh and nickel foam.
[0095] In some embodiments, the separator includes at least one of PP, PE, and a ceramic membrane. Preferably, the separator is PP.
[0096] In some embodiments, the electrolyte includes a lithium salt and a non-aqueous solvent.
[0097] In some embodiments, the lithium salt includes at least one of LiPF6, LiFSI, and LiTFSI. Preferably, the lithium salt is LiPF6.
[0098] In some embodiments, the non-aqueous solvent includes at least one of ethylene carbonate, ethyl methyl carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, and 1,3-dioxolane. Preferably, the non-aqueous solvent is a mixed solution of ethylene carbonate, ethyl methyl carbonate, and 1,3-dioxolane in a volume ratio of 3:3:4.
[0099] In some embodiments, the concentration of the lithium salt in the electrolyte is 0.5 mol / L-2 mol / L. As an example, the concentration of the lithium salt may be 0.5 mol / L, 1 mol / L, 1.5 mol / L or 2 mol / L. Preferably, the concentration of the lithium salt is 1 mol / L.
[0100] In some embodiments, the electrode plate can be prepared by the following method: the active material, binder, and conductive agent prepared by the above method are mixed evenly to obtain a viscous slurry; the viscous slurry is coated on the surface of the current collector and then pressed into sheets; and the electrode plate is obtained after the viscous slurry is dried.
[0101] In some embodiments, the solvent of the slurry includes at least one of anhydrous ethanol, water, and N-methylpyrrolidone (NMP).
[0102] In some embodiments, the drying temperature of the slurry is 60°C-120°C.
[0103] As an example, the drying temperature of the slurry may be 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, or 120°C.
[0104] In some embodiments, the drying time of the slurry is 1 h to 20 h.
[0105] As an example, the drying time of the slurry may be 1 h, 2 h, 4 h, 6 h, 8 h, 10 h, 12 h, 14 h, 16 h, 18 h or 20 h.
[0106] The scheme of the present application is described below by specific examples. It should be noted that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If no specific technology or conditions are specified in the examples, the technology or conditions described in the literature in this area or the product instructions are used. The reagents or instruments used are not specified by the manufacturer, and are all conventional products that can be obtained commercially.
[0107] Example 1
[0108] The preparation of the active material comprises the following steps:
[0109] S100, 0.5g of nucleating agent FeCl3 and 100g of water are prepared into a nucleating agent solution, 10g of biomass porous carbon is added to the nucleating agent solution and stirred to obtain a mixed solution; the mixed solution is dried until the water is removed to obtain a mixture; wherein the Dv50 particle size of the nucleating agent is 5nm, and the specific surface area of the biomass porous carbon is 600m 2 / g, the stirring speed of the stirring treatment is 100r / min, the stirring time is 6h, the stirring temperature is 25°C, and the drying temperature of the drying treatment is 100°C.
[0110] S200, placing the mixture in a tubular furnace, introducing a hydrogen-argon mixed atmosphere (hydrogen concentration is 5%) into the tubular furnace, heating the mixture to 800°C at a rate of 5°C / min, and then closing the outlet valve of the tubular furnace; continuing to control the ventilation pressure to 0.01MPa until the pressure in the tubular furnace reaches 0.02MPa, then closing the air inlet valve of the tubular furnace, and continuing to keep the temperature at 800°C for 2h; after the reaction is completed, cooling the reaction product to room temperature; washing the reaction product with 0.5mol / L hydrochloric acid solution, filtering it, and drying the filtrate to obtain an active material.
[0111] Preparation of negative electrode
[0112] The active material, conductive agent Super P carbon black, and binder carboxymethyl cellulose were added to an aqueous solvent in a weight ratio of 8:1:1, and then a small amount of anhydrous ethanol was used as a grinding aid; a planetary ball mill was used to mill at a speed of 200 rpm / h for 30 minutes to prepare a negative electrode slurry; the negative electrode slurry was evenly coated on the copper current collector with a scraper thickness of 150 μm, and dried at 80°C under vacuum conditions for 12 hours to prepare a 12 mm negative electrode sheet.
[0113] Battery Assembly
[0114] Using lithium sheets as counter electrodes and reference electrodes, the positive electrode sheets, negative electrode sheets, electrolytes and separators were assembled into 2016 button cells in a glove box with oxygen and water content less than 0.1 ppm; the separator was PP; the electrolyte was a LiPF6 solution with a LiPF6 concentration of 1 mol / L; the non-aqueous solvent was a mixed solution of ethylene carbonate (EC) and diethyl carbonate (DMC) in a volume ratio of 1:1; the additive was a mixture of 10% fluoroethylene carbonate (FEC) and 1% vinyl carbonate (VC).
[0115] The difference between Example 2 and Example 1 is that the calcination temperature in Example 2 is 1000°C.
[0116] The difference between Example 3 and Example 1 is that the temperature of the calcination treatment in Example 3 is 1300°C.
[0117] The difference between Example 4 and Example 1 is that the nucleating agent in Example 4 is 1 g CoCl2, and the pressure of the calcination treatment is 0.04 MPa.
[0118] The difference between Example 5 and Example 4 is that the pressure of the calcination treatment in Example 5 is 0.06 MPa.
[0119] The difference between Example 6 and Example 4 is that the pressure of the calcination treatment in Example 6 is 0.08 MPa.
[0120] The difference between Example 7 and Example 1 is that the nucleating agent in Example 7 is 2 g NiNO3, the calcination temperature is 1300°C, and the calcination pressure is 0.04 MPa.
[0121] The difference between Example 8 and Example 7 is that the calcination treatment time in Example 8 is 4 hours.
[0122] Example 9
[0123] The preparation of the active material comprises the following steps:
[0124] S100, 10g of biomass porous carbon and 1g of nucleating agent metal lithium were ground and mixed evenly in a glove box to obtain a mixture, wherein the grinding time was 30min; the specific surface area of the biomass porous carbon was 600m 2 / g.
[0125] S200, placing the mixture in a 30 mL reactor, introducing 3 mL of hydrogen-argon mixed atmosphere (hydrogen concentration is 5%) into the reactor, and then sealing the reactor;
[0126] The mixture was heated to 500°C at a rate of 5°C / min. At this time, the pressure in the reactor was 0.5MPa. The mixture was kept warm for 2 hours at a calcination temperature of 500°C. After the reaction was completed, the reaction product was cooled to room temperature. The reaction product was washed with 0.5mol / L hydrochloric acid solution, filtered, and dried to obtain an active material.
[0127] Preparation of electrode sheets
[0128] The active material, binder polyvinylidene fluoride (PVDF), and conductive agent Super P carbon black are added to NMP in a weight ratio of 8:1:1 and stirred to form a uniform viscous slurry. The viscous slurry is then coated on the surface of the current collector and pressed into sheets. After the sheets are dried at 80°C for 8 hours, they are cut into electrode sheets with a diameter of 16 mm.
[0129] Assembly of capacitors
[0130] The current collector-electrode plate-diaphragm-electrode plate-current collector are placed in the mold in the order, and then the electrolyte is injected between the electrode and the diaphragm with a rubber-tipped dropper to assemble the capacitor. Among them, the diaphragm is PP; the current collector is a stainless steel mesh; the electrolyte is a LiPF6 solution with a LiPF6 concentration of 1 mol / L, and the non-aqueous solvent is a mixed solution of ethylene carbonate, ethyl methyl carbonate, and 1,3-dioxolane in a volume ratio of 3:3:4.
[0131] The difference between Example 10 and Example 9 is that the nucleating agent in Example 10 is 1 g of metallic sodium, the amount of gas introduced is 50 mL, and the pressure is about 0.8 MPa.
[0132] The difference between Example 11 and Example 9 is that the nucleating agent in Example 11 is 3 g of metallic magnesium, the calcination temperature is 700° C., the gas introduced is 50 mL, and the pressure is about 1 MPa.
[0133] Comparative Example 1
[0134] Comparative Example 1: 10 g of untreated biomass porous carbon was directly used as the negative electrode material of the secondary battery and the material of the capacitor.
[0135] The difference between Comparative Example 2 and Example 5 is that, in Comparative Example 2, the gas outlet valve is not closed, and a protective atmosphere of 0.01 MPa is continuously introduced into the reaction system.
[0136] The difference between Comparative Example 3 and Example 5 is that the pressure of the calcination treatment in Comparative Example 3 is 1.5 MPa.
[0137] The difference between Comparative Example 4 and Example 10 is that the reactor in Comparative Example 4 is not inflated.
[0138] The difference between Comparative Example 5 and Example 10 is that the pressure of the calcination treatment in Comparative Example 5 is 1.5 MPa.
[0139] Performance Test:
[0140] 1. The specific surface area, electrical conductivity, and ID / IG of the active materials or porous carbons of Examples 1-11 and Comparative Examples 1-5 were tested.
[0141] 2. The button cells of Examples 1-8 and Comparative Examples 1-3 were subjected to electrochemical performance tests on a Xinwei battery testing system. The charge and discharge voltage range was 0V-2V, the current density was 0.2C, and 1C=1000mA / g.
[0142] 3. The performance of the capacitors of Examples 9-11, Comparative Example 1, and Comparative Examples 4-5 was tested. Since the assembly was a button-type structure, the test was conducted using a two-electrode system on a blue-electric test system, with a charge and discharge voltage range of 0V-1.6V and a current density of 50mA.
[0143] The test results of Examples 1-8 and Comparative Examples 1-3 are shown in Table 1.
[0144] Table 1
[0145]
[0146] As shown in Table 1, according to the specific surface area data, conductivity data, and ID / IG data of the porous carbon in Examples 1-8 and Comparative Example 1, it can be seen that the newly generated carbon material layer on the surface of the porous carbon can effectively block the open pores of the porous carbon, so the specific surface area of Examples 1-8 is smaller than that of Comparative Example 1; the newly generated carbon material layer has good conductivity, so the conductivity of Examples 1-8 is higher than that of Comparative Example 1; and the carbon material layer attached to the porous carbon can improve the surface defects of the porous carbon, so the ID / IG value of Examples 1-8 is smaller than the ID / IG value of Comparative Example 1.
[0147] The size of the first cycle charge capacity directly reflects the lithium storage capacity of the battery, and the lithium storage capacity is related to the pore structure and conductivity distribution of the negative electrode active material. By comparing the charge capacity data of Examples 1-8 and Comparative Example 1, it can be seen that the batteries prepared in Examples 1-8 have better electrochemical reaction activity.
[0148] According to the charging specific capacity data after ten cycles of Examples 1-8 and Comparative Example 1, it can be seen that the batteries prepared in Examples 1-8 have good cycle stability, which is related to the formation of a dense carbon material layer on the surface of the porous carbon in Examples 1-8. During the charge and discharge process, the dense carbon material layer can protect the structure of the porous carbon and reduce the degree of damage to the porous carbon structure. Therefore, the batteries prepared in Examples 1-8 have better cycle stability.
[0149] According to the data of the initial charge and discharge efficiency and the charge and discharge efficiency after ten cycles of Examples 1-8 and Comparative Example 1, it can be seen that the batteries prepared in Examples 1-8 have better electrochemical performance.
[0150] According to the specific surface area data, electrical conductivity data, and ID / IG data of the porous carbon in Example 5 and Comparative Examples 2-3, it can be known that during the calcination process, the appropriate calcination treatment pressure is 0.02MPa-1MPa; when the pressure is less than 0.02MPa (i.e., Comparative Example 2), the newly generated carbon material layer cannot well block the openings of the porous carbon, nor can it form a dense carbon material layer. Therefore, its specific surface area data, electrical conductivity data, and ID / IG data are worse than those of Example 5, which in turn causes the electrochemical performance and cycle stability of the battery in Comparative Example 2 to be worse than those of Example 5; when the pressure is greater than 1MPa (i.e., Comparative Example 3), the newly generated carbon material layer excessively blocks the openings of the porous carbon, and the newly generated carbon material layer is over-extended. Therefore, the pore structure of the porous carbon in Comparative Example 4 is worse than that in Example 5, which in turn causes the electrochemical performance and cycle stability of the battery in Comparative Example 3 to be worse than those of Example 5.
[0151] The test results of Examples 9-11, Comparative Example 1, and Comparative Examples 4-5 are shown in Table 2.
[0152] Table 2
[0153] sample <![CDATA[Specific surface area (m 2 / g)]]> Conductivity (S / cm) ID / IG Mass specific capacitance (F / g) Capacitance retention rate (%) Example 9 1868 6.83 1.88 191 85.3 Example 10 1846 7.21 1.76 190 85.4 Embodiment 11 1898 7.23 1.84 209 86.3 Comparative Example 1 1928 1.17 2.93 150 80.1 Comparative Example 4 1604 4.19 2.32 167 83.2 Comparative Example 5 1468 7.09 1.81 155 82.5
[0154] As shown in Table 2, according to the specific surface area data, conductivity data, and ID / IG data of the porous carbon in Examples 9-11 and Comparative Example 1, it can be seen that while a new carbon material layer is generated on the surface of the porous carbon, the molten nucleating agent promotes the reorganization of the newly generated carbon material structure, thereby increasing the degree of graphitization of the porous carbon, so the specific surface area of Examples 9-11 is smaller than that of Comparative Example 1; the newly generated carbon material layer has good conductivity, so the conductivity of Examples 9-11 is higher than that of Comparative Example 1; and the carbon material layer attached to the porous carbon can improve the surface defects of the porous carbon, so the ID / IG value of Examples 9-11 is smaller than that of Comparative Example 1. Therefore, according to the mass specific capacitance and capacitance retention rate data of the capacitor in Examples 9-11 and Comparative Example 1, a high mass specific capacitance means that the capacitor has a high energy density, and a high capacitance retention rate means that the capacitor has good cycle stability and long service life. The capacitors prepared in Examples 9-11 have higher energy density and better cycle stability.
[0155] According to the specific surface area data, conductivity data, and ID / IG data of the porous carbon in Example 10 and Comparative Examples 4-5, it can be seen that during the calcination process, the appropriate calcination treatment pressure is 0.02MPa-1MPa; when the pressure is less than 0.02MPa (ie, Comparative Example 4), or the pressure is greater than 1MPa (ie, Comparative Example 5), the degree of graphitization and the pore structure of the porous carbon are worse than those in Example 10, which in turn causes the energy density and cycle stability of the capacitor in Comparative Examples 4-5 to be worse than those in Example 10.
[0156] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A method for preparing an active material, characterized in that: include: The porous carbon and the nucleating agent are mixed to obtain a mixture; wherein the nucleating agent includes at least one of an alkaline earth metal, an alkali metal, and a transition metal salt; The mixed material is calcined to obtain the active material; wherein the pressure of the calcination is 0.02MPa-1MPa; and the temperature of the calcination is 300°C-2000°C.
2. The method according to claim 1, characterized in that The calcination temperature is 500°C-1300°C, and the calcination time is 0.5h-10h.
3. The method according to claim 1 or 2, characterized in that: The mass ratio of the porous carbon to the nucleating agent in the mixture is 1:(0.01-0.1).
4. The method according to claim 1 or 2, characterized in that: The transition metal salt includes at least one of chlorate, sulfate, nitrate and phosphate of the transition metal element; the transition metal element includes at least one of manganese, cobalt, nickel, iron, zinc and copper; and / or, The alkali metal includes at least one of metallic lithium, metallic sodium and metallic potassium; and / or, The alkaline earth metal includes at least one of metal magnesium and metal calcium.
5. The method according to claim 1 or 2, characterized in that: The Dv50 particle size of the nucleating agent is 1 nm-10 nm.
6. The method according to claim 1 or 2, characterized in that: The porous carbon includes at least one of biomass-based porous carbon, resin-based porous carbon, and petroleum asphalt-based porous carbon; and / or, The specific surface area of the porous carbon is 500 m 2 / g-1000m 2 / g.
7. The method according to claim 1 or 2, characterized in that: Before the calcination process, the method further comprises: drying the mixed material, wherein the drying temperature of the drying process is 80° C.-120° C.
8. The method according to claim 1 or 2, characterized in that: The method further includes post-processing the active material, wherein the post-processing step includes: washing the active material with an acidic solution.
9. An active material, characterized in that The method is prepared by any one of claims 1 to 8.
10. A secondary battery, characterized in that: The invention comprises a negative electrode plate, wherein the negative electrode plate comprises a negative electrode current collector, and a negative electrode active material layer located on at least one side of the negative electrode current collector, wherein the negative electrode active material layer comprises an active material prepared by the method according to any one of claims 1 to 8, or an active material according to claim 9.
11. A capacitor, characterized in that: It comprises an electrode plate, wherein the electrode plate comprises an active material layer, and the active material layer comprises an active material prepared by the method according to any one of claims 1 to 8, or the active material according to claim 9.